Desarrollo psicomotor y su relación con la alimentación en los niños de los CNH de la zona rural de Malacatos del MIES-Loja - Loaiza Manzanillas, Byron Fernando (2015)
This study entitled "PSYCHOMOTOR DEVELOPMENT AND ITS RELATIONSHIP WITH FOOD IN CHILDREN OF CNH AREA RURAL MALACATOS MIES-LOJA", aimed to determine the practices of infant feeding and young child and his influence on the development psychomotor, for which a transverse and correlational study was based on surveys of mothers of children enrolled in the program Growing with Our Children (CNH) of MIES-Loja Rural Malacatos 2014 where information was obtained from the power receiving children aged 0 to 36 months, from 120 children enrolled in the program CNH who met the inclusion criteria. To assess feeding practices, a survey was conducted, and based on the test psychomotor development was assessed Denver, obtaining the information necessary for our investigation. The results of this investigation in our study population showed that children who had an early start exclusive breastfeeding and breastfeeding 64% had normal psychomotor development assessment; in relation to children who had continued breastfeeding until 18 months 64% had normal results; Children who had timely complementary feeding from 6 months, 53% had a normal result; A similar result was observed in children older than six months who had a minimum dietary diversity had a normal outcome where 57%; in breastfed children who had a minimum frequency of meals 69% had a normal result, and with respect to children who had a minimum frequency of non-breastfed children meals in 52% of these patients had a normal test. Given the conclusion that infants and young children who had feeding practices as early initiation of breastfeeding, exclusive breastfeeding had better psychomotor development than those who did not. Keywords: Food, Psychomotor Development Test of Denver, Children under three years.